Question

Mathematics

See Answers

Best Answer

We can simplify the expression by combining like terms:

$(-7{x}^{2}+14+2x)+(10x+7-5{x}^{2})$ (-7x^(2)+14+2x)+(10 x+7-5x^(2))

$=-7{x}^{2}-5{x}^{2}+2x+10x+14+7$ =-7x^(2)-5x^(2)+2x+10 x+14+7

$=(-7-5){x}^{2}+(2+10)x+14+7$ =(-7-5)x^(2)+(2+10)x+14+7

$=-12{x}^{2}+12x+21$ =-12x^(2)+12 x+21

Therefore, the simplified expression is$-12{x}^{2}+12x+21$ -12x^(2)+12 x+21 .

Therefore, the simplified expression is

You might be interested in...

Explore more...